-63=4j(j-8)

Simple and best practice solution for -63=4j(j-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -63=4j(j-8) equation:


Simplifying
-63 = 4j(j + -8)

Reorder the terms:
-63 = 4j(-8 + j)
-63 = (-8 * 4j + j * 4j)
-63 = (-32j + 4j2)

Solving
-63 = -32j + 4j2

Solving for variable 'j'.

Reorder the terms:
-63 + 32j + -4j2 = -32j + 32j + 4j2 + -4j2

Combine like terms: -32j + 32j = 0
-63 + 32j + -4j2 = 0 + 4j2 + -4j2
-63 + 32j + -4j2 = 4j2 + -4j2

Combine like terms: 4j2 + -4j2 = 0
-63 + 32j + -4j2 = 0

Factor a trinomial.
(-9 + 2j)(7 + -2j) = 0

Subproblem 1

Set the factor '(-9 + 2j)' equal to zero and attempt to solve: Simplifying -9 + 2j = 0 Solving -9 + 2j = 0 Move all terms containing j to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 2j = 0 + 9 Combine like terms: -9 + 9 = 0 0 + 2j = 0 + 9 2j = 0 + 9 Combine like terms: 0 + 9 = 9 2j = 9 Divide each side by '2'. j = 4.5 Simplifying j = 4.5

Subproblem 2

Set the factor '(7 + -2j)' equal to zero and attempt to solve: Simplifying 7 + -2j = 0 Solving 7 + -2j = 0 Move all terms containing j to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -2j = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -2j = 0 + -7 -2j = 0 + -7 Combine like terms: 0 + -7 = -7 -2j = -7 Divide each side by '-2'. j = 3.5 Simplifying j = 3.5

Solution

j = {4.5, 3.5}

See similar equations:

| f(x)=6x-6f(10) | | 8(x+7)-8x=-8x+40 | | (x+38)+(x)=180 | | -16t^2-12t+52=0 | | 2n=(n+9) | | 5+2(x+1)=2x+7 | | x+3=SQRTx+7+(2) | | f(x)=0.5x-5f(14) | | 4x+9x-44=66-9x | | 10a-4b=10 | | -0.5x-2=7 | | -5x-5(2x-16)=155 | | 2(-4-5x)+6=2x-8 | | 6-(9-2)+3*6= | | -4x+20x=72 | | .8x+1.3=2x | | 172/-4+50-27=-20 | | 2(-4x-5)+6=2x-8 | | 9b^2-40=9+2b^2 | | 6x^2+53x-70=0 | | 38+7k=-8(k-4) | | 20=3z-4+9z | | f(x)=2x+5f(2) | | bc+x=xb+cx | | 2x+4=8-2x | | 3x-5(x+7)=-45 | | 3.4+10m=8.76 | | x^2-10x+18=20 | | 10t=-16t^2+12t+8 | | 6x+3(-3+10)=45 | | 6(36-10x)-8=-32 | | 4(f+2)+6=2(f-3)+5 |

Equations solver categories